STUDI SENAM ZUMBA SESAAT TERHADAP KADAR KOLESTEROL TOTAL PADA MAHASISWA JURUSAN GIZI POLITEKNIK KESEHATAN KEMENTERIAN KESEHATAN MANADO - Meildy E. Pascoal; Daniel Robert; Helke Poluan (POLTEKKES KEMENKES MANADO, 2014)
Regular physical activity is beneficial to regulate body weight and strengthening the heart andvascular system. The proportion of physical activity was classified as less active in general is26.1 per cent of the benefits of sport that lower total cholesterol, lower triglycerides, HDLhigher. In essence. The purpose of this study to determine gymnastics Zumba moment onlevels of total cholesterol.This research is descriptive where researchers want to know the benefits of exercise zumbaagainst total cholesterol levels in students from the Department of Nutrition Program DIIIpolytechnic studies manado. The research was conducted on June 4, 2015. The number ofsamples in this study were 30 people. Fat intake data was obtained using the form Recoll 24hours. The level of total cholesterol is done by using a measuring device that is Autochekcholesterol. Data on fat intake if using nutrisurvey and descriptive analysis.The results showed that 80% of 30 samples included in the category of normal totalcholesterol levels and 20% are included in the category of less than <100 mg / dl. While the fatintake of 30 samples of 27% in the high category, 10% included in the normal category and63% included in the category less.